La Universidad y los regimenes militares - Meschkat, Klaus (La Sociología en sus Escenarios, 2010)
Abstract. Conference of professor Klaus Meschkat in the University of Conception, Chile on the occasion of a tribute that the University does to him by its quality of ex professor of the Institute of Sociology, that in 1973 was exonerated and detainees by the military administration of the institution. Professor Meschkat it makes a parallel between which it happened in the european universities during the implantation of facismo and what happened in the Chilean universities during the military dictatorship. Also, ask for a public recognition to all the professors expelled, exonerated and detainees during the military dictatorship protests. Resumen. Conferencia del profesor Klaus Meschkat en la Universidad de Concepción, Chile con motivo de un homenaje que la Universidad le hace por su calidad de ex - profesor del Instituto de Sociología, quien en el año 1973 fue expulsado y detenido por la Administración militar. Profesor Meschkat hace un paralelo de lo que sucedio en la universidades eurropeas con la instauración del facismo y lo sucedido en las universidades chilenas con la dictadura militar. Igualmente, reclama un reconocimiento público a todos los profesores expulsados, exonerados y detenidos durante la dictadura militar.